MORPHOLOGICAL CHARACTERISTICS AND REPRODUCTIVE ORGANS ASSESSMENT OF BLUE-SPOTTED MUDSKIPPER Boleophthalmus boddarti IN PENINSULAR MALAYSIA - Nur-Hidayah Mohd Nor; Syazwin-Rafhanah Saifuzzaman; Izzati Adilah Azmir; Norjasmin Hussin (BIOTROPIA, 2023)
Mudskippers have a unique adaptation allowing them to live on the land and commonly inhabiting the mangrove ecosystem. A fundamental study on the Blue-spotted mudskippers, Boleopthalamus boddarti were purposely to identify the species through morphometric and meristic characteristics, observation on the gonad organs as well as to correlate with their length-weight relationship. Collection of B. boddarti (n=72) from Matang Perak, Pendas Johor and Pekan Pahang was conducted using hand and net. Data collection on seventeen morphometric and seven meristics characters, length and weight, and pictorial documentation on male and female gonads were conducted. The means of each characteristic were estimated by using analysis of Variance (ANOVA) with P<0.05. The morphometric analysis found eye diameter and posterior dorsal fin ray count characteristics were significantly different (P<0.05) followed by five meristics characteristics except for anterior dorsal fin ray count and upper jaw teeth characteristics (F value ≥ 1.0). The mature gonad of female B. boddarti was found with an ovary in bright yellow coloration, turgid, firm and visible presence of eggs. Male gonads were identified with a testis having two lobes, a swollen structure at the top of the elongated shape and appear pale pink and thicker than the immature testes that generally exist in string-like structures. The length and weight of the fish were found directly proportional to the regression curve displayed b≠3. Morphometric and meristic characteristics were a reliable method in the identification of fish in general and for B. boddarti in specific. The observation of gonads differentiation helps understand the mature and immature state of the sex organs. This study offered an easy, quick and low-cost approach in determining species and sexes compared to the molecular method.